2013
DOI: 10.1073/pnas.1308450110
|View full text |Cite
|
Sign up to set email alerts
|

FtsK-dependent XerCD- dif recombination unlinks replication catenanes in a stepwise manner

Abstract: In Escherichia coli, complete unlinking of newly replicated sister chromosomes is required to ensure their proper segregation at cell division. Whereas replication links are removed primarily by topoisomerase IV, XerC/XerD-dif site-specific recombination can mediate sister chromosome unlinking in Topoisomerase IV-deficient cells. This reaction is activated at the division septum by the DNA translocase FtsK, which coordinates the last stages of chromosome segregation with cell division. It has been proposed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
82
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(90 citation statements)
references
References 32 publications
7
82
0
1
Order By: Relevance
“…This suggestion is consistent with the previous result that the formation of the XerCD-dif synapsis is independent of FtsK C (24). FtsK can resolve catenated chromosomes produced by replication (41). We have previously suggested that FtsK may facilitate this decatenation by remaining in the vicinity of XerCD-dif after the activation of recombination and activating multiple rounds of recombination (12,24).…”
Section: Resultssupporting
confidence: 92%
“…This suggestion is consistent with the previous result that the formation of the XerCD-dif synapsis is independent of FtsK C (24). FtsK can resolve catenated chromosomes produced by replication (41). We have previously suggested that FtsK may facilitate this decatenation by remaining in the vicinity of XerCD-dif after the activation of recombination and activating multiple rounds of recombination (12,24).…”
Section: Resultssupporting
confidence: 92%
“…Remarkably, a similar reconnection pattern (which brings the trefoil knot to the Hopf link, the unknot and the unlink of two smaller unknotted loops) is also shown to characterize DNA recombination: quite remarkably, a mathematically rigorous characterization of the topological mechanism of DNA unlinking is shown to be the only possible pathway that strictly reduces complexity by stepwise unlinking (Shimokawa et al 2013). The mathematics behind this proof suggests that it would be equally applicable to flux tube reconnections.…”
Section: New Insight Into Fluid-mechanical Behaviourmentioning
confidence: 78%
“…An intriguing problem is how proteins that are much smaller than the large DNA molecules on which they act manage to resolve topological exigencies rather than exacerbate them. In their recent work, Shimokawa et al address a particular aspect of this problem (2).…”
mentioning
confidence: 99%
“…The proof of theorem 2 is based on a classic invariant called the "signature," which for a link L is the difference between the number of positive and negative eigenvalues of a matrix associated to the surface bounded by L. Shimokawa et al (2) show that the absolute value of the signature for any link L, jσ(L)j, is at most c(L) − 1, where c(L) is the crossing number of L. The authors further show that (2m)-torus links and (2m − 1)-torus knots are special in that they realize the equality, jIσ(L)j = c(L) -1. Finally, by combining their tangle model for XerCD action with a theorem from knot theory (7), the authors establish that the signature of the product goes down by, at most, one for a single round of enzyme action.…”
mentioning
confidence: 99%
See 1 more Smart Citation